2001
DOI: 10.1186/1751-0147-42-311
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Copper Deficiency, Chromium Deficiency and Additional Molybdenum Supplementation in Goats – Pathological Findings

Abstract: Secondary copper (Cu) deficiency, chromium (Cr) deficiency and molybdenosis (Mo) has been suggested to cause the "mysterious" moose disease in the southwest of Sweden. The present experiment was performed on goats to investigate the clinical, chemical, and pathological alterations after 20 months feeding of a semi-synthetic diet deficient in Cu and Cr. Four groups were included in the study: control group (n = 4), Cu-deficient group (group 1, n = 4), Cr-deficient group (group 2, n = 2) and Cu+Cr-deficient grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Aside from cerebral edema, cerebellar hyperplasia in gelatinous material-filled cavities, demyelination in the brain, cerebellum, and medulla spinalis and wallerian degeneration have also been reported in animals with swayback [ 12 ] but this was not seen in our study. On the contrary, we observed neural chromatholysis, pyknosis, and satellitosis in the medulla spinalis similar to that resulting from Cu deficiency as previously reported by different authors [ 3 ].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Aside from cerebral edema, cerebellar hyperplasia in gelatinous material-filled cavities, demyelination in the brain, cerebellum, and medulla spinalis and wallerian degeneration have also been reported in animals with swayback [ 12 ] but this was not seen in our study. On the contrary, we observed neural chromatholysis, pyknosis, and satellitosis in the medulla spinalis similar to that resulting from Cu deficiency as previously reported by different authors [ 3 ].…”
supporting
confidence: 91%
“…Glial cell proliferation was observed in grey matter of the spinal root pyknosis and chromatholysis of the neurons were also noted in the same area. These findings were previously reported in goat kids, lambs, and calves with Cu deficiencies [ 3 , 14 ].…”
supporting
confidence: 88%
“…In ruminants it has been demonstrated that high levels of dietary MO can interfere with microbial metabolism [4,5]; however, information about the effect of MO on the poultry microbiota is limited. In this study, we observed that exposure to high MO levels resulted in lower Firmicutes and higher Proteobacteria abundance, whereas in the TP and MO + TP groups, an increase in Firmicutes abundance and Firmicutes/Bacteroidetes ratio at phylum level was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, MO (45 mg/kg BW) can also have negative effects as demonstrated in several studies where rumen microbial metabolism was altered. Moreover, MO (100 mg/kg diet) can interfere with the bioavailability of other trace elements, such as iron (Fe) and zinc (Zn), especially copper (Cu) leading to Cu deficiency [3,4,5,6]. Other adverse effects that have been observed in animals exposed to high dietary levels of MO include poor growth, achromotrichia, severe diarrhea, and anemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Histological analyses have demonstrated that the seminiferous tubules of Cu-deficient animals are less developed. This was mainly explained by the inactivation of the function of the Sertoli cells [48,50,[58][59][60][61]. All these data indicate that copper concentration and metabolism in male gonads must be very tightly regulated, starting from puberty and continuing progressively throughout adult life.…”
Section: Dysfunction Of Spermatogenesis In Both Copper Overload and Deficiencymentioning
confidence: 99%